Beyond 2030: structures for achieving sustainable development - Cernev, Tom; Fenner, Richard (Frontiers in Climate, 2024)
With 2030 quickly approaching and hence the end of the Sustainable Development Goal (SDG) timeline, it is necessary to start the conversation as to what the post-2030 international development goals, that will take over from the SDGs, will look like. Building on the experiences of implementing the Millennium Development Goals (MDGs) and SDGs, there is the possibility of making the post-2030 goals the most efficient and successful to date. This perspective explores the lessons that have been learnt from the MDGs and SDGs, and together with a consideration of emerging global trends develops proposals for post-2030 goals and targets. In total seven goals are suggested: (1) Operate within planetary boundaries (2) Create growth within resource limits (3) Provide access to basic services for all (4) Eliminate poverty and hunger (5) Reduce inequality (6) Deliver good health and education for all (7) Build strong institutions and international partnerships. The goals are categorised as being: (i) Environmental and Economic (ii) Physical Assets (iii) Social, and (iv) Collaboration. System interdependencies and possible causal connections between the proposed post-2030 goals are also explored. A novel approach of five yearly assessments of the risks involved if the targets are not met, together with suggestions for corrective action is discussed, which will help inform governments and decision makers of the urgent actions needed. To avoid a disruptive future, careful formulation of the post SDG period beyond 2030 is urgently needed to provide a fair and consistent framework to hold both government and industry to account at local, national, and international levels. This will require the strengthening of existing international institutions and strategies for the financing of development.